Sequence variation patterns along a latitudinal cline in Scots pine (Pinus sylvestris): signs of clinal adaptation? - Kujala, Sonja T; Savolainen, Outi (Tree genetics & genomes, 2012)
Adaptive clinal variation is abundant in nature, and its genetic basis is of great interest. The polygenic nature of this variation poses a challenge for identifying the causative loci underlying these adaptations. Here, we have examined the patterns of sequence variation in ten candidate genes for timing of bud set and cold tolerance, traits that form strong latitudinal clines in Scots pine (Pinus sylvestris). A set of reference genes was used for comparison and to infer a simplified demographic background model with approximate Bayesian computation methods. Against the resulting bottleneck model, the neutrality tests show little signs for local adaptation, but species-wide selection is suggested in some of the studied genes. In line with the theoretical expectations, we see little evidence for adaptive differentiation with F ST methods. Instead, allele frequency clines were found in three genes (dhn1, ftl2, and prr1). Our results add to the discussion on which molecular signals best characterize a gene subject to clinally varying selection. This will be especially relevant when these kinds of observations can be examined in parallel with association study results.